Discovery of a recombination dominant plasma: a relic of a giant flare of Sgr A*?. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Nakashima, S.; Nobukawa, M.; Uchida, H.; Tanaka, T.; Tsuru, T. G.; Koyama, K.; Uchiyama, H.; Murakami, H.
Abstract: We present the discovery of out-flow like plasma emissions with the Suzaku and ASCA data. Those plasmas have a size of ∼150 pc. Remarkably, the southern plasma is in a recombination dominant phase, which is not predicted by standard shock heating. A plausible scenario is either photoionization due to strong jet-like X-rays from Sgr A* or rapid cooling due to adiabatic expansion of a blowout plasma from the Galactic center about 10 5 years ago.